(untitled) (Archives of Criminology, 1988)
The paper contains the results of a questionnaire study carried out on national representative samples of family courts judges (277 persons) and voluntary probation officers (247 persons). The main aim of the study was to obtain the practicians opinion as to the model of probation service existing in Poland and its ideal vision, as well as the conception of the work of a voluntary probation officer with a juvenile delinquent and his milieu and the: effectiveness of such work. comparing the statements of judges and voluntary probation officers, the author intended to find out what opinion the persons who play various parts in the process of resocialization of juveniles have on the educational work of voluntary probation officers: what this work should be and what it actually is. The picture that emerges from the statements of both groups of respondents is not favourable, the appraisals made by family courts judges being more, critical as a rule than those of voluntary probation officers. Some of the respondents statements are declarations and wishes. Over a half of the family courts judges (58 per cent) and about 80 per cent of voluntary probation officers consider the voluntary-cum-professional model of probation service for juvenile delinquents found in our country to be a good one (although only a part of them approve of it fully, with the remaining ones accepting it conditionally and submitting various proposals for its improvement). On the other hand, as many as 42 per cent of judges and about 20 per cent of voluntary probation officers opt for the performance of supervision -by professional probation officers only. To substantiate their standpoint, these persons argue that voluntary probation officers lack qualifications, are insufficiently engaged in educational work with juveniles, and that in their case difficulties arise in executing the proper performance of supervision. Also the enrollment of voluntary probation officers is disapproved of, the examined persons stating that in the face of a small number of applicants for this work, no requirements can be imposed upon them, and many of them are chance persons with no training whatever. As few as 7.6 per cent of family courts judges and as many as 48.6 per cent of voluntary probation officers are of the opinion that probation officers are well prepared to perform their function of resocialization. In the opinion of most respondents, the number of voluntary probation officers is greatly insufficient. The author was also interested in the respondents vision of the voluntary probation officer’s work with a juvenile and his milieu, the elements that should prevail in this work: education, care or supervision, and the actual situation in this respect, as well as the real course of this work. Most respondents (78 per cent of judges and 52.2 per cent of probation officers) stresed the educational elements of a voluntary -probation officer’s activity. :What is alarming, however, is the fact a considerable group both of family courts’ judges (21.3 per cent) and of voluntary probation officers (30 per cent) believe formal supervision to be the most important aspect. Yet as shown by the findings of the study, the actual work of .a voluntary probation. officers departs greatly from the declared ideal model. Voluntary probation officers are burdened with an excessive number of supervised juveniles, with about 30 per .cent of them supervising over 10 persons which is the number set as the maximum. The majority of respondents demand a reduction of the number of juveniles under supervision, which is however difficult to be fulfilled because of the lack of candidates willing to become probation officers. As appears also from the respondents statements, there is no elaborate conception of the voluntary probation officer’s work. Too much weight is attached when appraising this work to its formal criteria (e.g. the number of probation officer’s contacts with the juvenile). Instead, the quality of his work is inadequately analyzed. Admittedly, both professional probation officers and most of all family courts judges lack sufficient data to carry out such an analysis: namely, the information about a voluntary probation officer’s work come from his reports that are frequently faulty as regards quality, contents and promptness; this appears not only from the judge’s but also from the voluntary probation officers’ own statements. Co-operation between voluntary probation officers on the one hand, and profesional probation officers and family courts’ judges on the other hand, is also faulitly organized. The respondents perceive this co-operation as the opportunity to settle definite legal, educational and organizational matters rather, than as a regular influence of the family court towards an improvement of the voluntary probation officers’ qualifications and an increase of their educational impact on the juveniles. In resocializing activities, great weight is attached to the educational methods applied by the voluntary probation officer. His basic method is considered to be that of individual therapy which should be accompanied by group and environmental therapy. As appears from the statements of most voluntary probation officers, the forms of their work, and of influencing the juvenile in particular, were rather modest and poorly differentiated, the probation officers revealing litt1e initiative and being either relucant or unable to make the contacts with juvniles supervised by them more diversified. As few as about 20 per cent of the examined voluntary probation officers were in good contact with some of their probationers at any rate, the contact being of a therapeutical character (which was important in so- far as over 40 per cent of probation officers stated that they supervised- juveniles with personality disorders). In resocializing work, the posibilities of influence in a group of young persons are insufficiently used. Moreover, voluntary probation officers meet with many difficulties in co-operating with their probationers families, their contacts with the institutions engaged in crime prevention, education or social assistance being also unsatisfactory. Voluntary probation officers co-operate rather regularly with schools, the police, the Polish Committee for Social Aid and occupational guidance centres only (though naturally the degree of a voluntary probation officer’s co-operation with the abovementioned institutions differs). The respondents of both groups expressed their opinions about the effectiveness of the supervision, its conditions and criteria. In general, views of family courts judges and of volunatry probation officers converged to a high degree, the majority of respondents being of the opinion that nothing but the juvenile’s complete and positive participation in the social life and proper performance of due social roles testifies to a successful ending of a supervision. Convergences could also be found. between the judges and the probation officers opinions about the conditions of success vs. failure of supervision. Discussing successful supervisions respondents of both groups stressed the importance of good relations between the probation officer and his probationer, co-operation with the juvenile’s parents, their emotional commitment and readiness to act jointly with the probation officer, the probation officer’s competence in getting into emotional contact with the juvenile and his family and to win their confidence. According to the respondents, the most important factors that determine a failure of supervision are: the juvenile’s considerable demoralization, influence of the negative peer group, a negative family milieu and a lack of co-operation. with the probation officer on the part of the parents. Therefore, respondents of both groups lay a great emphasis on the importance of emotional relations which should link the three parties involved: the juvenile, his parents, and the voluntary probation officer. The necessity of mutual approval, understanding and respect for each other’s rights, was particularly stressed. Mutual good emotional relations linking the above-mentioned persons seams to be the key issue as far as success or failure of super- vision is concerned. If both the juvenile and his parents have a favourable attitude towards the probation officer and trust him, it will be much easier for him to persuade the juvenile of the necessity of regular learning or changing his conduct, and his parents-of the need for co-operation. Therefore the findings point to the fact that the declared shape of the work of a voluntary probation officer is much better than the actual one. The final part of the questionnaire was devoted to the use of educational measures and obligations of juvenile delinquents and their parents resulting from provisions of the Act of Nov. 26, 1982 on the proceedings in cases concerning minors. The Act introduced new educational measures and obligations of juveniles, as well as the possibility of punishing the juvenile’s parents with a fine and notifying their workplaces or social organizations they are members of about their failure in parental obligations whenever this failure is caused by the parents fault. About 60-70 per cent of the judges never applied the newly introduced educational measures nor imposed obligations upon juveniles, although over a half of the judges and 60-70 per cent of the voluntary probation officers are convinced that it was right to introduce these new measures. A part of the respondents however (one-fourth of the judges and one-fifth of the probation officers) express their doubts as to the possibilities of the family court’s supervision of performance of the obligation imposed upon juveniles. Very few judges applied disciplinary measures towards the juveniles parents in practice, although about 25 per cent of them express an opinion as to the effectiveness of a fine, and about 18 per cent believe that notifying the parents workplace may bring about satisfactory results. As compared with judges, voluntary probation officers expressed their favourable opinion as to the effectiveness of these measures more frequently (44 and 62 per cent respectively). Because of a relatively short period of binding force of the new provisions (which was about one and a half years at the moment of the study), the problem of application of some of the educational measures and obligations in particular, as well as the judges and probation officers opinion as to their pertinence and the possibilities of supervising their execution should be investigated further.